TRICHOMES MORPHOLOGY ON PETALS OF SOME ACANTHACEAE SPECIES - Muhammad Amirul Aiman Ahmad Juhari; Noraini Talip; Che Nurul Aini; Mohamad Ruzi (REINWARDTIA, 2014)
A preliminary taxonomic study was carried out on seven Acanthaceae species namely as Andrographis paniculata,Pseuderanthemum graciliflorum,P. carruthersii, Asystasia gangetica ssp. micrantha, Ruellia repens, Justicia comata and J. betonica.The study was undertaken to investigate the morphology of trichomes present on the surfaces of flower petal. The variations found in this study are in their types and density. Based on observation, two forms of trichomes are present in all species studies which are glandular and non-glandular trichomes. There are seven types of trichomes found in this study. Trichomes types are shown to have systematic significance that can be used to differentiate and identify certain Acanthaceae species studied.